2018
DOI: 10.1055/s-0038-1648247
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Oriented Preoperative Radiologic Evaluation in Cochlear Implantation - Our experience with a Proposed Checklist

Abstract: Introduction Preoperative temporal bone imaging studies have been routinely performed prior to cochlear implantation. Radiologists need to report these examinations with special focus on the surgeon's expectations. Objectives To provide a basic structured format, in the form of a checklist, for reporting preoperative computed tomography (CT) and to its clinical impact on operative findings. Methods The preoperative temporal bone CT scans of 47 patients were analyzed and reported accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…During mastoid surgeries and transmastoid approaches, a lowlying or overhanging tegmen can obscure the antrum and SCC and impede the identification of important anatomical landmarks, thereby predisposing patients to higher risks of intraoperative complications such as facial nerve ablation and labyrinth injury. 16,18,20 Sloping of the tegmen has also been shown to obstruct transmastoid access to the attic when managing cholesteatoma endoscopically. 15 As the tegmen is encroached on the tympanic ring, the SSC is expected to be more difficult to visualize during SCD repairs, especially when performed via the transmastoid approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During mastoid surgeries and transmastoid approaches, a lowlying or overhanging tegmen can obscure the antrum and SCC and impede the identification of important anatomical landmarks, thereby predisposing patients to higher risks of intraoperative complications such as facial nerve ablation and labyrinth injury. 16,18,20 Sloping of the tegmen has also been shown to obstruct transmastoid access to the attic when managing cholesteatoma endoscopically. 15 As the tegmen is encroached on the tympanic ring, the SSC is expected to be more difficult to visualize during SCD repairs, especially when performed via the transmastoid approach.…”
Section: Discussionmentioning
confidence: 99%
“…LLT has been regarded as an anatomical obstruction of the surgical field during otologic procedures. During mastoid surgeries and transmastoid approaches, a low‐lying or overhanging tegmen can obscure the antrum and SCC and impede the identification of important anatomical landmarks, thereby predisposing patients to higher risks of intraoperative complications such as facial nerve ablation and labyrinth injury 16,18,20 . Sloping of the tegmen has also been shown to obstruct transmastoid access to the attic when managing cholesteatoma endoscopically 15 .…”
Section: Discussionmentioning
confidence: 99%
“…14 and further studied for cochlear implantation by Mandour et al . 1 Whereas Sun et al . did not correlate their radiological findings with intra-operative findings, Mandour et al .…”
Section: Discussionmentioning
confidence: 99%
“…An anteriorly placed sigmoid sinus represents surgical restraints while performing posterior tympanotomy and accessing the round window. Our method to infer sigmoid sinus position is in conjunction with the method proposed by Sun et al 14 and further studied for cochlear implantation by Mandour et al 1 Whereas Sun et al did not correlate their radiological findings with intra-operative findings, Mandour et al found significant correlation between the two. Both these studies have utilised two additional lines on high resolution CT and have graded the sigmoid sinus position.…”
Section: Sigmoid Sinus Positionmentioning
confidence: 95%
See 1 more Smart Citation